Unlocking the potential of rice field ponds for rural communities in Cambodia - Sean, Vichet (CGIAR, 2024)
Rice field fisheries have long been an essential part of Cambodia’s rural landscape, providing crucial sustenance and income to millions of people. With this, the CGIAR Initiative on Asian Mega-Deltas (AMD) has been leading the charge in conducting transformative experiments aimed at harnessing the potential of rice field ponds to improve the livelihoods of rural communities and contribute to sustainable development.